Evaluation of a Saccharomyces cerevisiae Fermentation Product on the Feedlot Performance and Carcass Merit of Hair Lambs Offered an Annual Ryegrass-Hay-Based Finishing Diet: A Pilot Study - Justin C. Burt; Jamie A. Boyd; Lisa L. Baxter; Ivan A. Garcia-Galicia; Brittany P. Kerley (Animals, 2023)
Hair sheep production has increased in recent years, which has resulted in an increased presence in feedlots. Additionally, grass-based finishing systems for ruminant animal production have increased. Data are limited for finishing hair lambs on diets based on cool-season hay. The objective was to evaluate a Saccharomyces cerevisiae fermentation product (SCFP) on the feedlot performance and carcass characteristics of Katahdin lambs offered an annual ryegrass (Lolium multiflorum)-hay-based diet. Twenty-four Katahdin lambs (21.5 ± 2.5 kg BW) were assigned to either the control (CON) or the yeast-supplemented group (SCFP) in a completely randomized design. Lambs were offered a 14% crude protein total mixed ration diet based on annual ryegrass hay. The SCFP group also received the yeast supplement in their diet. Lambs in the SCFP group had a higher final body weight (p < 0.01) and ADG (p = 0.01). Less maximum and total energy were required to cut SCFP lamb meat compared to CON lamb meat (p < 0.03). Results from this study indicated that SCFP supplementation may prove to be beneficial in hair lamb finishing diets. Future research will need to specifically evaluate the use of these products in hair lambs with a larger sample size.